Bahasa Arab dan Perkembangannya di Sudan - Ahmad Musyarraf Irfam (Journal of Arabic Education and Linguistics, 2023)
Arabic is the national language in more than 25 countries in the Middle East. One of these countries is the Republic of Sudan, where the majority of the population is Muslim. Sudan is a unique country as it brings together two cultures, Arab and African. Therefore, this research aims to provide an overview of Sudan, the process of Islam and Arabic language entering Sudan, as well as the development of Arabic language in Sudan. This writing is based on the principles of historical methodology, starting with heuristic, criticism, interpretation, and historiography. Sudan gained its sovereignty and became an independent country on January 1, 1956. It is located in Northern Africa with its capital city in Khartoum. The population consists of Arabs (39%), Beja (6%), and various local African tribes (52%). The introduction of Islam and Arabic language in Sudan is closely related to the spread of Islam in Africa and the Arabization of Sudan, leading to the massive development of the Arabic language over the years. The entry of Islam and Arabic language in Sudan is closely linked to the spread of Islam in Africa until its independence. As a result, there has been significant development of the Arabic language over the years, with the emergence of various Arabic language educational institutions in the country.